“Bendito e louvado seja”: os benditos como elemento de construção da romaria de São Severino do Engenho Ramos – Paudalho/PE - Silva, Leonardo Ferreira da (2019)
The present work is a master's research the central theme of which is the relationship between music, represented by the collective song called bendito, and the construction of the pilgrimages to the São Severino do Engenho Ramos Sanctuary, in the city of Paudalho, in the State of Pernambuco. From an ethnomusicological perspective, the work was guided by the general objective of understanding in what form and to what extent the musical performance, embodied by the intonation of the benditos, contributes to the process of construction of this pilgrimage. The theoretical basis of this research draws from the field of Ethnomusicology, Anthropology, Religion Sciences and other related areas. The methodological procedure for the research was within an ethnographic approach, based on field research and using multiple data collection instruments, namely participant observation, semi-structured interviews, audio and video recordings and photographs. Benditos can be defined as songs of oral tradition sung in thirds, novenas, processions, funeral ceremonies and pilgrimages. These songs constitute one of the most representative vocal genres within the universe of popular Catholicism, having in its poetic content an essentially saintly character. The work is structured in two main parts; the first one consists of three chapters that discuss conceptual questions concerning field research and ethnographic writing in the field of Ethnomusicology, the basic concepts of research and, finally, the historical and geographical context in which this pilgrimage occurs, as well as peculiar characteristics of the devotion to the martyr São Severino. In the second part, also structured in three chapters, we bring descriptions and analysis of the field experiences with the pilgrims, always focusing on the relationship between this musical practice and the construction of the pilgrimages to Santuário de São Severino do Engenho Ramos. Based on the field experiences, together with the dialogue with the interdisciplinary literature used in this research, we conclude that the musical performance, located in the singing of the bendito, plays a structuring role in all of the ritual process, making it indispensable for the development and construction of the pilgrimages to the Santuário de São Severino do Engenho Ramos. This function of structure of the pilgrimage implies a range of roles played by this music throughout the process of the pilgrimage, understood as a ritual performance that is characterized by the pilgrimage to the encounter of the sacred.